Zeolitic imidazolate framework-8 as an efficient and facile heterogeneous catalyst for the acceptorless alcohol dehydrogenation to carboxylates; Journal of Catalysis; Vol. 417 - Gu Jun-Fei; Chen Cheng; Zheng Zhong-Hui; Hang Jing; Wei Sang; Wang Ji-Chao; Yuan Ye; Chaemchuen Somboon; Verpoort F. V. K. Frensis Valter Kornelius (2023, 2023)
Title screen